(untitled) (Sciences & Technologie. C, Biotechnologies, 2014)
Bovine paratuberculosis is an infectious and contagious chronic disease due to the multiplication of the mycobacterium M paratuberculosis in the organism. This disease is widespread in all countries practicing intensive cattle raising and causes heavy economic losses. The objective of this study is to search for paratuberculosis in cattle in the slaughterhouses. The practical part consists on severalvisits to the slaughterhouse, to inspect the intestines, totake samples from the mesenteric hypertrophied ganglions, with a portion of the intestine, and to send them to the laboratory for histopathological study. Two stains were made, the HE and cold Ziehlstain; impressions of intestines and mesenteric ganglions are also colored by the Ziehl-Neelsen hot method and examined microscopically.